FAKTOR RESIKO UMUR DAN PARITAS IBU BERSALIN DENGAN KEJADIAN RUPTUR PERINEUM DI PUSKESMAS BAAMANG I SAMPIT TAHUN 2019 - vina anggraini (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
RISK FACTORS OF MATERNITY AGE AND PARITY WITH PERINEAL RUPTURE IN PUBLIC HEALTH CENTER BAAMANG I SAMPIT 2019 ABSTRACT Vina Anggraini(1) Background : Perineal Rupture is an injury to the birth path that occurs at the time of the baby’s using either tools or not using a tool . The cause of maternal death in indonesia related to pregnancy and childbirth is caused by hemorrage. Postpartum hemorrhage is one of them from laceration of the birth canal or Perineal Rupture. Based on the results of research conducted by researchers at Puskesmas Baamang I Sampit in June to September 2020 the number of maternity mothers who experienced a Perineal Rupture in 2019 as many as 73 people out of 197 mothers in childbirth. The Study Found : Knowing the Risk Factors of Maternity Mother's Age and Parity with Perineal Rupture Event at Puskesmas Baamang I Sampit Year 2019. Metoden Research : This research uses retrospective quantitative approach analytics methods with cross sectional research design. Conducted at Puskesmas Baamang I Sampit in June - September 2020 with a sample of 73 people using the Technique Total Sampling from secondary data. Variables are age-free and parity and variables are bound to the Perineal Rupture event. The Result : The result of the bivariate analysis use the chi square test and the different test x2 (2x2) from 73 maternity mothers, the risk factor for the age at risk of the maternal is 1 times likely at risk of Perineal Rupture than the age of the birth mother is not at risk with value (? value : 1.000 and OR value : 1,104) and the risk factor for parity at risk is 0,164 times likely at risk of Perineal Rupture compared to maternity mothers with no risk parity with value (? value : 0.002 and OR value : 0,164). Conclusion : Age and parity on maternal are the risk factors of Perineal Rupture. Keywords : Risk, Factors, Age, Parity, Perineal Rupture Lecturer Of Midwifery Academy Muhammadiyah Kotim